Associated factors and outcomes of crossover from a laser sheath to a bidirectional rotational mechanical sheath during transvenous lead extraction - Tsuyoshi Isawa; Taku Honda; Kazuhiro Yamaya; Shigeru Toyoda; Masataka Taguri (Journal of Arrhythmia, 2023)
Abstract Background During transvenous lead extraction (TLE), a GlideLight laser sheath (Philips) cannot always be advanced over the lead, and crossover to the Evolution system (i.e., an Evolution RL sheath or Evolution Shortie RL sheath [Cook Medical]) is required. We aimed to determine the associated factors and outcomes of such device crossover. Methods This observational study included 112 patients who underwent TLE. The patients were divided into crossover and non‐crossover groups. Outcomes and associated factors of crossover were evaluated. Results Overall, 57 (50.9%) patients required crossover to the Evolution system (crossover group), whereas 55 (49.1%) patients did not require crossover (non‐crossover group). Clinical success rate was similar between the two groups (98.3% vs. 100%; p = 1.00). No major intraprocedural complications related to powered sheaths occurred. Multivariate logistic regression analysis results showed that dwell time of the oldest extracted lead (per year) (odds ratio [OR]: 1.18, 95% confidence interval [CI]: 1.02–1.36; p = .026), number of leads extracted per procedure (OR: 7.23, 95% CI: 1.74–29.99; p = .007), and use of a femoral approach (OR: 21.09, 95% CI: 2.33–190.67; p = .007) were associated factors of crossover. The cutoff for crossover was 7.7 years from the implant (sensitivity 90.5%, specificity 64.9%, area under the curve 0.80). Conclusions Both groups showed a high rate of clinical success. Switching to the Evolution system may facilitate a safe and effective TLE when a laser sheath does not advance despite laser activation.